Pengaruh Suhu Sintering Pada Pembuatan Prototipe Replika Tulang Berbasis Hidroksiapatit Dengan Metode Starch Consolidation - Adi Mulyadi Putra; Aman Aman; Ahmad Fadli (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
3D bone replica based on porous Hydroxyapatite (HA) is a candidate bone implant material that has similarities to the original bone. Starch consolidation is one of the methods for making HA scaffold The purpose of this research are to determine the effect of sintering temperature on porous HA characteristics. This research was conducted by mixing 20 grams of HA with 8 grams of sago starch and 25 ml of distilled water to form slurry. The slurry formed was then stirred at 400 rpm. The mixture was then put into a mold. Then the mixture in the mold was heated to 100oC for 60 minutes. After that, the green bodies are removed from the mould and dried in an oven at 80°C for 24 hours and 110°C for 8 hours. The dried sample is then put into the furnace. Combustion is carried out at a temperature of 600˚C and ended with sintering at a temperature of 1250˚C with the increasing rate of sintering temperature at 2°C/minute and holding time for 1 hour. The higher the sintering temperature causing the density, shrinkage and bending stress to be greather. Sintered bodies show density in the range of 2.52-2,56 gr/cm3, shrinkage 35.87–39.47% and bending stress 4,026.49 MPa. Keywords: bending stress; bone replica; hydroxypatite; sintering